The program for the development of readiness for the implementation of educational work of future teachers of musical art with schoolchildren - Kuznetsova, O. (Problems of Engineer-Pedagogical Education, 2021)
The article presents the results of the author's development of pedagogical criteria and indicators of readiness for musical and educational activities of future teachers of musical art with students, namely: motivational and cognitive, which is characterized by the criterion of the degree of motivation for the implementation of musical and educational activities with students; reflective component with reflectivity as a criterion; cognitively oriented, which is expressed in awareness and instrumental armament in the methods and forms of musical educational work; communicative-empathic component, expressed in terms of the degree of development of empathy, communicative and organizational abilities; creative and active with such criteria as abnotivity, creativity and aesthetic abilities. The author experimentally confirmed the effectiveness of the developed and tested methodological system for preparing future music teachers for educational work with schoolchildren. The effectiveness of the formative experiment was confirmed, which took place in three stages: information-organizational, aimed at the formation of motivational-cognitive and reflective-conscious components, operationally integrated, aimed at the development of cognitive-oriented and communicative-empathic components, as well as creatively representative, aimed at the formation of reflective-conscious and creatively active components. The experimental group recorded a statistically significant increase in the indicators of motivation to participate in music education with schoolchildren, awareness of the methods and forms of music education, non-verbal creativity, reflectivity, empathy, organizational and communication skills, aesthetic abilities and abnotivity, and in the control group the level of these indicators have not changed. Attracting students to the system of preparation for musical and educational work had a positive effect on any conditions of readiness for this type of professional activity, especially on the indicators of motivational and organizational-creative criteria.